Electronic origin of negative thermal expansion in V2OPO4. Issue 48 (12th May 2020) - Pachoud, Elise; Cumby, James; Wright, Jon; Raguž, Branimir; Glaum, Robert; Attfield, J. Paul
Abstract : Unusual negative thermal expansion in V2 OPO4 is discovered to arise from phase coexistence around the charge ordering transition at 605 K. Abstract : Negative volume expansion between 620 and 800 K in V2 OPO4 is discovered to be of electronic origin due to the charge ordering transition at 605 K. Domain reorientation and coexistence of the low and high temperature phases close to the transition are observed in X-ray diffraction data from single crystals grown by chemical vapour transport.